Pascal’s Wager and Its Postmodern Counterpart - Nyman, Bill (Koers (Potchefstroom, South Africa), 2024)
Pascal’s Wager is probably the most analysed apologetic argument in the history of apologetics. What has often been the case, however, is that this piece of Pascal’s Pensées has often been misinterpreted and taken out of the Pascal’s total apologetic work. For that reason, the Wager has been misappropriated and has undergone a battery of misplaced criticism. Taken in its proper context, the Wager is a beautiful vindication of the Christian faith, cleverly constructed to make the sceptic re-think his position and contemplate the importance of the Christian faith. Much confusion exists about the placement of this particular Pensées, and where it is situated in his overall apology (Pensées 418) lends itself to the challenge of what has become “the Many Gods Objection.” For that reason, I would suggest that Pascal’s Wager belongs at the very beginning of his Pensées, where the rest of the Pensées are an explanation for the reason Christianity is the most attractive belief. Postmodern philosophers have re-appropriated the Wager and made it fit their own philosophical and theological presuppositions playing in the hands of the “Many-Gods-Objection.” This paper describes the beauty of Pascal’s Wager in its proper context and expresses the erroneous postmodern appropriation of the Wager.